METABOLIC PROFILING AND CYTOTOXIC ACTIVITY OF METHANOL EXTRACTS FROM CHAMAECRISTA DUCKEANA (P. BEZERRA & A. FERN.) H. S. IRWIN & BARNEBY (LEGUMINOSAE, CAESALPINIOIDEAE) - Daniele Rodrigues de Lima; Maria Gleiziane de Araújo Franca; Fátima de Cássia Evangelista de Oliveira; Cláudia do Ó Pessoa; Alberto José Cavalheiro; Maria Goretti de Vasconcelos Silva (Química Nova, 2022)
The genus Chamaecrista comprises more than 330 species, with only a few studies on their chemical composition and biologic activities. In this study, the phytochemical profile of leaf, stems, and fruits extracts of the C. duckeana were examined by UPLC ESI HRMS analysis to determine possibly bioactive constituents. The antioxidant activity was carried out through in vitro assay, by the sequestration of the free radical DPPH. To evaluate the cytotoxic activity of the extracts, an MTT assay was used and the IC50 was determined against HL60 and RAJI cell lines. The metabolic profiles of the botanical parts are dominated by flavonoid class, highlighting isoflavonoids such as daidzin and ononin. All these compounds are reported for the first time in C. duckeana. The extracts presented antioxidant potential, and the activity of the stems extract was higher than the standard butylated hydroxytoluene. In the cytotoxic assay, only HL60 line (leukemia) had growth inhibition over 80%. The stems presented more expressive cytotoxicity with IC50 of 137.3 (104.6-180.1) and 106.8 (96.52-118.3) μmol. L-1 for HL60 and RAJI, respectively. In conclusion, the present work provides an in-depth knowledge about the chemical profile of C. duckeana, a species rich in bioactive secondary metabolites with cytotoxic activity.